An ultra-thin LC resonator structure for radar cross section reduction - Goyal A.; Singh K.P.; Singh S.P. (My University, 2025)
In this paper, an ultra-thin LC resonator structure operating in X-band is designed which is intended to be used as a shield to reduce the radar cross section of a conducting plate. The proposed structure is simulated using Ansoft HFSS software which shows an absorption peak at 8.125 GHz with reflection coefficient of -34.2 dB. The LC structure constructed from resistive/low conductivity material is backed by a grounded foam material. The results show that the proposed absorber offers reduction in radar cross section (RCS) for the conducting plate over the frequency range 7.38-9.45 GHz. Moreover, the structure has the thickness of 3 mm which is only 0.0738λ and 0.0945λ at the lowest and highest frequencies respectively. The real and imaginary parts of the normalized impedance are unity and zero respectively at the resonant frequency. We can shift the absorption frequencies by varying the gap as well as length-segment of the Meander line structure. © 2014 IEEE.